Movement patterns of African elephants (Loxodont africana, Blumenbach) in a seasonally variable ecosystem in south-eastern Chad - Labuschagne, Zanne Claire (Percy FitzPatrick Institute of African Ornithology, 2015)
Includes bibliographical references.